2014
DOI: 10.1007/s11071-014-1632-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel framework to design and compare limit cycle minimizing controllers: demonstration with integer and fractional-order controllers

Abstract: In this paper, a constrained optimization problem is formulated to tune the limit cycle minimizing controllers meeting additional loop-shaping performances such as phase margin and gain crossover frequency. A graphical approach is proposed so as to determine the superior controller in terms of better limit-cycle suppression. The framework is illustrated with a suitable case of elementary servo plant which has separable static backlash nonlinearity in its model. For this plant, integer-order controllers and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The appropriateness of the proposed variants of the SOA in designing the FOPI controller is also compared with other global optimization techniques (DE [11] and CMAES [12]) and popular classical local search techniques (Nelder-Mead simplex search (NM-SS) [9] and interior point method (IPM) [10]) in Table 3. It can be observed that the CSOA outperforms the other algorithms under consideration, while the ESOA is better than the other algorithms except for the CSOA and is comparable to DE.…”
Section: Soamentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriateness of the proposed variants of the SOA in designing the FOPI controller is also compared with other global optimization techniques (DE [11] and CMAES [12]) and popular classical local search techniques (Nelder-Mead simplex search (NM-SS) [9] and interior point method (IPM) [10]) in Table 3. It can be observed that the CSOA outperforms the other algorithms under consideration, while the ESOA is better than the other algorithms except for the CSOA and is comparable to DE.…”
Section: Soamentioning
confidence: 99%
“…Optimization techniques have been widely adopted for designing FO controllers. In [6,7,9,10], local searchbased techniques were applied for fast tuning of FO controllers. However, their performance was sensitive to the selection of the initial feed point and the solutions obtained were prone to getting trapped into local optima.…”
Section: Introductionmentioning
confidence: 99%
“…In Oliveira et al (2003, 2006, 2012), effective use of DF for the synthesis of controllers to meet the desired limit cycle details is studied. This theory is extended to tune the fractional order controllers (FOCs) and integer order controllers (IOCs) to suppress the limit cycle magnitude by proposed optimization problem (Kesarkar et al, 2014, 2015) in addition to meet the desired specifications for system with single nonlinearity. Lanusse and Oustaloup (2004, 2005) also suggested a FOCs with an anti-windup feature for plants with input saturation nonlinearity.…”
Section: Introductionmentioning
confidence: 99%